Agri-Environmental Policies in a Transition Economy: Using a Choice Experiment to Value Agricultural Biodiversity on Hungarian Small Farms - Ekin Birol; Ágnes Gyovai; Melinda Smale (Fondazione Eni Enrico Mattei (FEEM), 2004)
Agricultural biodiversity is a crucial environmental resource. Much of the agricultural biodiversity remaining today is found on the semi-subsistence farms of poorer countries and on the small-scale farms and home gardens of more industrialised nations. The traditional Hungarian home gardens, which serve as small farms, are an example. Historically, these home gardens have served important functions related to food security, diet quality, and local culture. Some policies related to European Union accession threaten the survival of traditional home gardens in Hungary's transitional economy. This paper applies the choice experiment method to estimate the value farmers themselves attach to the agricultural biodiversity still found in these micro-agroecosystems. One of several related studies, its aim is to enhance policy understanding of the role of Hungarian small farms and home gardens in the National Agri-Environmental Programme. The analysis is based on primary data collected in three environmentally sensitive areas of Hungary where pilot agri-environmental programmes have been initiated. Findings demonstrate the variation in values farmers assign to home gardens across regions and households, with implications for the design of efficient public conservation programmes.
Keywords: Q12; Q18; Q26; 330; Agricultural biodiversity; Conservation; Choice experiment method; Hungary; Home garden; Artenvielfalt; Agrarpolitik; Landwirtschaftlicher Familienbetrieb; Nebenerwerbslandwirtschaft; Ungarn